Kinetic and combustion characteristics of oil palm empty fruit bunch biochar using thermogravimetric analysis - Pansawati, Indah Sakina; Agustin, Yustika; Ahda, Yusuf (Jurnal Teknosains, 2024)
The usage of renewable energy is a mitigation phenomenon majorly impacting the power sectors, with biomass being one of the sources directly replacing coal in various applications. This leads to the portrayal of biomass having the potential to be a carbonaceous material, namely the Empty Fruit Bunch (EFB) of oil palm. To increase the characteristics of EFB, it can be converted into carbon-based products through thermochemical processes, such as hydrothermal carbonization. Therefore, this study aimed to compare the characteristics of feedstock and biochar EFB using the TGA method. The heating rate used in this study is 10 – 30°C/min at five °C/min intervals. The effect of heating rate on kinetic parameters and thermal (DTG, TGA) and combustion (T ignition, T burn out) characteristics was also determined. This study carried out the HTC process at temperatures of 210ᵒC and 230ᵒC. The results showed that biochar EFB had a higher ignition, burnout temperature, and activation energy than raw EFB. Ignition temperatures for EFB-HT210°C and EFB-HT230°C were 297°C and 298°C; burnout temperatures for EFB-HT210°C, EFB-HT230°C were 407°C and 450°C; and the activation energy for EFB-HT210°C, EFB-HT230°C were 58.84 kJ/mol and 62.16 kJ/mol. Besides the characteristics of biomass, the heating rate also affects combustion. This proved that increased heating rate caused higher ignition and burnout temperature and decreased activation energy. The results also indicated that the difference in heating rate influenced the peak temperature in DTG.